Physical control of the Lesser Grain Borer Rhyzopertha dominica (Coleoptera: Bostrychidae) using various microwaves levels - Ali, Azher M. (Journal of Kerbala for Agricultural Sciences, 2022)
This study was conducted in the year 2022 at the Department of Plant Protection, College of Agricultural Engineering Sciences, to evaluate the effect of microwave rays on various stages of the R. dominica. Microwaves of 220, 420 and 620 Watts at 30, 60 and 90 seconds effects on eggs, 4th instar larva, Pupas and adults were evaluated. The highest egg mortality was at 620 Watts for 60 seconds. Exposure to 620 Watts for 30 seconds increased the hatching period from 7.0 days for the control to 10 days 4th. Instar mortality was 100% at 620 Watt for 90 seconds. Pupae and adults 100 % mortality achieved at exposure to 620 Watts for 60 and 90 seconds, respectively. Generally, various stages of the R. dominica mortality increase by increasing the wattage and exposure time.